Acetylene blockage technique as a tool to determine denitrification potential of a biomass fixed on an organic media treating wastewater. Issue 5 (1st September 2006) - Le Bihan, Y; Gilbert, Y; Lessard, P
Abstract : Biofiltration on organic media is used in many wastewater applications. However, no tools are available to survey the microorganisms' activity inside the process. The acetylene blockage technique was adapted to evaluate the potential denitrifiers' activity. The objectives of this work were to adapt and verify the applicability of the method by evaluating its sensitivity and variability. A closed cell was built and installed in an open network where pure gaseous nitrogen and acetylene had been successively injected at fixed rate on filtering media samples. N2 O produced by the denitrifying biomass was monitored during the test. Assays were realized in replicates, with different quantities of filtering media, to observe the sensitivity and the variability of the method. Potential denitrifying activity and quantity of biomass correlation shows that the adapted method was sensitive for 50 to 150 g (wet basis) of filtering media. Moreover, when under an acetylene atmosphere, the coefficients of variation observed for the tests varied between 10% and 32% when under anoxic conditions. This work shows that the technique as adapted could be used as a tool to survey the potential activity of denitrifiers fixed on an organic media.